Efektivitas dan Kendala Terhadap Pemungutan Pajak Sarang Burung Walet di Kota Parepare - Bym, Ernita Ramadhani; Miftahul Jannah, Siti Hudzaifah; Yafid, Bunyamin (Muhammadiyah Law Review Journal, 2025)
State revenue is one of the sources of income allocated to fund various development programs. As a form of regional autonomy, regional tax collection is returned to the region which then has the authority to use regional original income for development in the region. The economic potential in a region can lead to contributions to the region, in Parepare City one of these potentials is the swallow's nest, so that Regional Government Regulation Number 1 of 2014 concerning the Swallow's Nest Tax was issued. With the aim of analyzing the collection of bird's nest tax and the obstacles experienced, this study uses an empirical legal approach and data analysis from various literature and empirical sources to align the suitability of applicable regulations and real events in the field. The results of this study indicate that the regulations that have been set have been implemented properly, but the obstacles faced in collecting bird's nest tax lie in public awareness, lack of public understanding, and the competence of tax officials and employees in persuading swallow's nest entrepreneurs, causing some of them to neglect paying taxes. It is considered that tax officials and employees need to take intense action both to improve public understanding and to increase public awareness